2017
DOI: 10.1002/2016jb013646
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic characterization of crack damage evolution in sandstone deformed under conventional and true triaxial loading

Abstract: We present a comparative study of crack damage evolution in dry sandstone under both conventional (σ1 > σ2 = σ3), and true triaxial (σ1 > σ2 > σ3) stress conditions using results from measurements made on cubic samples deformed in three orthogonal directions with independently controlled stress paths. To characterize crack damage, we measured the changes in ultrasonic compressional and shear wave velocities in the three principal directions, together with the bulk acoustic emission (AE) output contemporaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(47 citation statements)
references
References 53 publications
5
42
0
Order By: Relevance
“…However, in this study we are concerned with the evolution of crack damage that precedes ultimate failure. Our findings clearly show that such damage is a distinctly directional phenomenon, especially under true triaxial stress states (Browning et al, ). The fundamental and intrinsic attribute of any tensor invariant, that it is identical under any geometrical transformation, only serves to conceal the significance of this specific directionality (e.g., of sequentially evolving damage populations) with respect to the principal stresses and their orientations.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…However, in this study we are concerned with the evolution of crack damage that precedes ultimate failure. Our findings clearly show that such damage is a distinctly directional phenomenon, especially under true triaxial stress states (Browning et al, ). The fundamental and intrinsic attribute of any tensor invariant, that it is identical under any geometrical transformation, only serves to conceal the significance of this specific directionality (e.g., of sequentially evolving damage populations) with respect to the principal stresses and their orientations.…”
Section: Discussionsupporting
confidence: 72%
“…In the first of the three cycles, once a differential stress (Δ σ ) of 36 MPa has been reached, cracks form essentially parallel to σ zz and open essentially perpendicular to σ xx and σ yy and so are drawn as a colored girdle of poles in the x ‐ y plane. The breadth of the girdle is represented as 36° since it has previously been recognized that all fractures in the population do not form perfectly parallel to σ 1 but over a range of angles of about ±18° either side of σ 1 (see Browning et al, ). In the subsequent cycle, cracks form parallel to σ xx and open perpendicular to σ zz and σ yy , so this damage is represented as a girdle in the z ‐ y plane (with the same width of 36°) but is additional to the previous damage in the x ‐ y plane which remains.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclic loading and unloading tests with acoustic emission monitoring are an effective approach to quantitatively measuring deformation and damage characteristics of various materials [11][12][13][14][15][16][17][18][19][20]. Sherif et al [12] captured and analyzed AE signals to characterize the crack formation and crack width development in the cyclic loading processes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the fibre-reinforced composites and metallic materials, the AE method also is applied to research the mechanical behaviors of rock material. Browning et al [16] used cumulative AE hits and AE hits rate to evaluate the onset and evolution of new crack damage caused by inelastic processes in rocks under different loading conditions. Trippetta et al [17] found that there is a certain relation between the AE energy and the elastic moduli of seismogenic Triassic Evaporites subjected to cyclic stressing.…”
Section: Introductionmentioning
confidence: 99%